Volume 6: Energy 2022
DOI: 10.1115/imece2022-94528
|View full text |Cite
|
Sign up to set email alerts
|

Producing High-Strength Pellets From Seaweed, Sawdust, and Hay for Gasification

Abstract: Hay, invasive lupine plants, wood chips, and seaweed are the four abundant biogenic fuel options in Iceland. These four biomass types are potential renewable fuel feedstock as they can be converted into syngas or high-value fuels using thermochemical processes such as pyrolysis and gasification. In this study, we focus on biomass pelletizing, which is a major process for preparing various kinds of feed for either gasification or controlled combustion as in powerplants and heat applications. Pelletizing is prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Pradhan, Mahajani and Arora (2018), the moisture range is 15 to 23%, and a particle size of less than 6.5 mm is required for pellet processing. In addition, Nazemi et al (2022) suggested that 20% of sawdust with wheat straw can enhance pellet strength. Also, additives proportion of 0.5 to 5% (total mass fraction) can improve pellet quality (Tabil 1996).…”
Section: Blending Materials Selection and Proportionmentioning
confidence: 99%
“…According to Pradhan, Mahajani and Arora (2018), the moisture range is 15 to 23%, and a particle size of less than 6.5 mm is required for pellet processing. In addition, Nazemi et al (2022) suggested that 20% of sawdust with wheat straw can enhance pellet strength. Also, additives proportion of 0.5 to 5% (total mass fraction) can improve pellet quality (Tabil 1996).…”
Section: Blending Materials Selection and Proportionmentioning
confidence: 99%